Success Rate of Intact Canal Wall Tympanoplasty in Safe Type of Chronic Suppurative Otitis Media’ Patients - Sukma Nisa Janitra; Artono (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Surgical therapy for chronic suppurative otitis media (CSOM) is by tympanoplasty with orwithout mastoidectomy. The purpose of surgery is to eradicate the source of infection. Success indicatorsof tympanoplasty are achieving dry ears without recurrent otorrhea, myringoplasty, and an increase in thehearing threshold.Objectives: is to know the success rate of intact canal wall tympanoplasty in safe type CSOM patients.Methods: Retrospective descriptive was used in this study. All safe-type of CSOM patients undergoing intactcanal wall tympanoplasty surgery from January to December 2018 at Dr. Soetomo General Hospital were usedas the participant data.Results : There were 32 participants, divided into a higher proportion of males than females (ratio 1.1:1). The characteristics of the participants included; the most age group were 21-30 years (37.50%), originoutside Surabaya (59.37%), and high school education level (62.50%). Most perforations were subtotal(40.63%) and hearing loss was conduction (62.50%). Apparently, 56.25% were patent Eustachian tubes,90.63% were sclerotic mastoid Schuller photographs, and 62.50% were granulation tympanic cavity findings.Additionally, 78.13% were performed tympanoplasty type 1. The results of postoperative eradication showeddry ears (84.38%) and successful of myringoplasty (71.88%). The mean increase in the hearing threshold forAC, BC, and ABG after surgery was 15.98 dB, 4.57 dB, and 11.40 dB.Conclusion: The results of eradication after intact canal wall tympanoplasty were mostly dry ears, successfulmyringoplasty, and an increase in the mean hearing threshold of AC, BC, and ABG.